Description of the first cryptic avian malaria parasite, Plasmodium homocircumflexum n. sp., with experimental data on its virulence and development in avian hosts and mosquitoes. Issue 1 (January 2015) - Palinauskas, Vaidas; Žiegytė, Rita; Ilgūnas, Mikas; Iezhova, Tatjana A.; Bernotienė, Rasa; Bolshakov, Casimir; Valkiūnas, Gediminas
Graphical abstract: Highlights: We provide information about cryptic speciation of avian malaria parasites. Plasmodium homocircumflexum (pCOLL4) is a highly virulent malaria parasite. Exoerythrocytic stages of P. homocircumflexum are formed in various organs. Anemia and cerebral paralysis cause death in experimentally infected canaries. Abstract: For over 100 years studies on avian haemosporidian parasite species have relied on similarities in their morphology to establish a species concept. Some exceptional cases have also included information about the life cycle and sporogonic development. More than 50 avian Plasmodium spp. have now been described. However, PCR-based studies show a much broader diversity of haemosporidian parasites, indicating the possible existence of a diverse group of cryptic species. In the present study, using both similarity and phylogenetic species definition concepts, we believe that we report the first characterised cryptic speciation case of an avian Plasmodium parasite. We used sequence information on the mitochondrial cytochrome b gene and constructed phylogenies of identified Plasmodium spp. to define their position in the phylogenetic tree. After analysis of blood stages, the morphology of the parasite was shown to be identical to Plasmodium circumflexum. However, the geographic distribution of the new parasite, the phylogenetic information, as well as patterns of development of infection, indicate that this parasite differs from P. circumflexum . Plasmodium homocircumflexum n. sp. was described based on information about genetic differences from described lineages, phylogenetic position and biological characters. This parasite develops parasitemia in experimentally infected birds – the domestic canary Serinus canaria domestica, siskin Carduelis spinus and crossbill Loxia curvirostra . Anaemia caused by high parasitemia, as well as cerebral paralysis caused by exoerythrocytic stages in the brain, are the main reasons for mortality. Exoerythrocytic stages also form in other organs (heart, kidneys, liver, lungs, spleen, intestines and pectoral muscles). DNA amplification was unsuccessful from faecal samples of heavily infected birds. The sporogonic development initiates, but is abortive, at the oocyst stage in two common European mosquito species, Culex pipiens pipiens (forms pipiens and molestus ) and Aedes vexans. Vectors of this Plasmodium sp. remain unknown.